ANALISIS KADAR LOGAM BERAT PB DALAM PELEMBAP KULIT DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (AAS) - Marta, Rahmat Raighend; Iskandar, Damaiyanti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Cosmetics are widely used in daily life; however, some products may contain hazardous chemicals such as the heavy metal lead (Pb). Lead is often found in cosmetics due to its ability to provide a brightening effect on the skin in a short period, but it poses significant health risks, including kidney damage and nervous system disorders. This study aims to determine the concentration of Pb in hand and body lotion products using the Atomic Absorption Spectrophotometry (AAS) method. Observations were conducted at the Cosmetic Chemistry Laboratory of BBPOM Palembang by following the analysis process from sample preparation to result interpretation using the AAS instrument. The test results showed that handbody samples 1 and 3 had safe Pb levels, while handbody 2 contained Pb concentrations close to the maximum limit set by BPOM (20 mg/L), though still within the safe range. The elevated Pb content is suspected to originate from pigments, raw water, or contamination from production equipment. This study highlights the importance of monitoring heavy metal contamination in cosmetics to ensure consumer safety